Isolasi dan Identifikasi Fraksi Toksik Ekstrak Tumbuhan Iler (Coleus scutellarioides [L.] Benth) - MADE DIRA SWANTARA (Indonesian Journal of Cancer)
Coleus scutellariodes L, Benth, locally known as Iler, has been traditionally used as medicines such as for treatment of fever, ears infection, diabetes, and dyspepsia. The polar constituents in Iler extracts are believed can inhibit the growth of leukemia cell. This research aims to isolate and identify any toxic compounds from toxic fraction of Iler which could be potential as anticancer agents. Extraction of metabolites from Iler leaves was carried out at room temperature using maceration methods with 85 % ethanol eluent. The crude extract was then fractionated into n-hexane, chloroform, and ethyl acetate respectively. Both extract and fractions were tested towards Artemia salina. The most active fraction was purified on silica gel column chromatography using n-hexane:chloroform (2:1) as eluent. Four compounds were identified in the most toxic fractions (LC50 90.72) using Gas Chromatography-Mass Spectrometry as palmitic acid ( 24.41), stearic acid (19.53%), 9-Octadecenamide (22.95%), and hexadioic acid, diocttyl ester (33.11%).